High-gain PDMS-magnetite zero refractive index metamaterial antenna for Vehicle-to-Vehicle communications - Noorlindawaty Md. Jizat; Nazihah Ahmad; Zubaida Yusoff; Mohd Faizal Jamlos (Bulletin of Electrical Engineering and Informatics, 2019)
This paper presents the simulation design of a high-gain antenna using zero refractive index fishnet metamaterial (MTM) perforated on PDMS-Magnetite substrate for Vehicle-to-Vehicle (V2V) communications. In order to design the MTM, magnetite nanoparticles, 10-nm iron oxide (Fe3O4) are dispersed into polydimethylsiloxane (PDMS) matrix. Subsequently, the unit cell is designed by removing the circular hole with radius of 3.69 mm on the PDMS-Magnetite substrate layer and arranged in 5×5 array fishnet configuration. This optimized MTM is inserted between the antenna design and pure PDMS substrate to improve the gain. The characteristic of the respective unit-cell is investigated to operate at 5.9 GHz and the effectiveness of MTM is performed by comparing the antenna performance with and without MTM. The unique characteristics of zero refractive index transform the diverging wave into plane wave for perfectly parallel wave impact on the design to improve the directivity and gain of the antenna. The proposed MTM into design improves the antenna gain to 7.36 dB without having to compromise other antenna parameters of return loss, Voltage Standing Wave Ratio (VSWR), gain, directivity, efficiency, current distribution, radiation pattern and bandwidth. These advantages has made proposed antenna as a suitable candidate for V2V in Dedicated Short Range Communication (DSRC) application since high-gain directional antenna is required to increase the sensitivity towards signals coming from certain direction.